2015
DOI: 10.1111/juaf.12096
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Geographically Targeted Economic Development Programs in Ohio

Abstract: Despite the continued popularity of spatially targeted industrial incentives with policymakers, a growing body of scholarship assessing outcomes associated with these policies has called their effectiveness into question. However, existing studies have treated different programs as comparable entities, when programs often differ markedly among each other in incentive generosity and requirements. This article uses panel data from 2000–2004 to examine county‐level employment and wage growth outcomes for Ohio's t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Interestingly, Anderson and Wassmer (2000) found that a local abatement to manufacturing property in the Detroit Metropolitan Area correlated with greater value of manufacturing property and lower property tax rates in the municipality offering them, but only in the early years of their granting before competing municipalities did the same. Hultquist’s (2014) research is a more recent example of the use of multiple regression analysis to detect the economic impact of incentives. It is highly relevant to this study, due to its examination of the impact of Ohio’s EZ and Job Creation Tax Credit (JCTC) programs on employment and wage growth in Ohio zip codes between the years of 2000 to 2004.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, Anderson and Wassmer (2000) found that a local abatement to manufacturing property in the Detroit Metropolitan Area correlated with greater value of manufacturing property and lower property tax rates in the municipality offering them, but only in the early years of their granting before competing municipalities did the same. Hultquist’s (2014) research is a more recent example of the use of multiple regression analysis to detect the economic impact of incentives. It is highly relevant to this study, due to its examination of the impact of Ohio’s EZ and Job Creation Tax Credit (JCTC) programs on employment and wage growth in Ohio zip codes between the years of 2000 to 2004.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies focus on the same EZ program, but draw different or conflicting conclusions. Examples include studies of the California program (Bostic and Prohofsky, 2006; Moore, 2003; Neumark and Kolko, 2010), of the Kentucky program (Lambert and Coomes, 2001; Zhang, 2015), and of the Ohio program (Ham et al., 2011; Hultquist, 2015; Landers, 2006). These results support the argument that methodology or research design may have possible roles in EZ research conclusions.…”
Section: The Ez Literaturementioning
confidence: 99%
“…Zhang (2015) evaluates industry-specific impacts of the Kentucky program on agriculture, manufacturing, trade, public administration, and service activities. Hultquist (2015) focuses on the impacts of the Ohio EZ program on manufacturing and transportation, and uncovers positive impacts on manufacturing growth. Moore (2003) suggests that the California EZ program had positive impacts on small firms with less than 9 employees, or large firms with 500–999 employees.…”
Section: Research Design Factorsmentioning
confidence: 99%
“…Later reforms called for a more fundamental restructuring of government institutions and redevelopment efforts. These reforms centered on four key themes: (i) augmenting the role of private‐sector credit and investment in generating targeted economic development (Hall, ; Porter, , ); (ii) calling on public agencies to behave more like and coordinate more with private‐sector businesses in economic revitalization (Mossberger, ; Osborne & Gaebler, ); (iii) defining redevelopment in terms of geographic region rather than target populations (Rich, ; Spindler & Forrester, ); and (iv) using tax expenditures in lieu of direct budget allocations (Hultquist, ). These four strategies contributed to new redevelopment approaches and programs, such as NMTC.…”
Section: The Road To Public–private Redevelopmentmentioning
confidence: 99%